Cost, Risk Management, Planning and Scheduling of Industrial Machine Foundation: Managing and Mitigating Risks in Industrial Machine Foundation Construction (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Machine Foundations forms viral and expansive part of any industrial complex, with rapid pace of industrial growth of any country. Machine foundation are made in such a way that they can support Static load, in addition to static load the dynamic forces caused by the working of Machine. Theses Dynamic Static forces are in turn, transmitted to the foundation of machine. While Construction these types of foundation accuracy is the first priority, machine‘s leg (foot) should be at right place as per the machine drawing this become a challenging job, various type of risk is involved and their mitigation technique are mention.